1987
DOI: 10.1007/bf02535544
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of ether phospholipids and analogs in neoplastic cells

Abstract: The ether phospholipid 1‐O‐octadecyl‐2‐O‐methyl‐rac‐glycero‐3‐phosphocholine (OM‐GPC) is known to be a potent inhibitor of cell growth. Metabolic studies in both Raji and L1210 leukemic cells on OM‐GPC,3H‐labeled in the methyl groups of the choline moiety, showed a (diacyl)‐phosphatidylcholine as the only labeled metabolite. Since the formation of radiolabeled (diacyl)‐phosphatidylcholine showed a direct correlation with cell death, we tested other lipid analogs. One of these compounds, hexadecylphosphocholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…This effect is currently under study for combination chemotherapy with DNA-interactive anti-HIV nucleoside analogs. Based on the hypothesis that degradation of certain ALP analogs by a phospholipase C is required for the generation of toxic metabolites (Fleer et al, 1987), Eibl and co-workers have synthesised derivatives of ether lipids such as a series of alkylphosphocholines (APC). One of the most active APC is hexadecylphosphocholine (D 18506, Asta-Werke, Germany), which is depicted in Figure 1.…”
Section: Development Of New Ether Lipidsmentioning
confidence: 99%
“…This effect is currently under study for combination chemotherapy with DNA-interactive anti-HIV nucleoside analogs. Based on the hypothesis that degradation of certain ALP analogs by a phospholipase C is required for the generation of toxic metabolites (Fleer et al, 1987), Eibl and co-workers have synthesised derivatives of ether lipids such as a series of alkylphosphocholines (APC). One of the most active APC is hexadecylphosphocholine (D 18506, Asta-Werke, Germany), which is depicted in Figure 1.…”
Section: Development Of New Ether Lipidsmentioning
confidence: 99%
“…Thus, it seems that there is not a marked enantiomer specificity in the ET-18-OCH 3 action that could suggest a lack of stereospecific interactions with a macromolecular target. It has been reported that ET-18-OCH 3 can be a substrate for a phospholipase C-like enzyme, able to split off or exchange the phosphocholine moiety, leading to the notion that the generation of 1-O-octadecyl-2-O-methyl-rac-glycerol could be responsible for the cytotoxic properties of ET-18-OCH 3 [65,66]. However, we found no apoptotic effect when HL-60 cells were treated with a number ET-18-OCH 3 -or ET-16-OCH 3 -derived diglycerides and analogues [15], indicating that the products generated by a phospholipase C-mediated degradation of ET-18-OCH 3 are unable to induce an apoptotic response.…”
Section: Structure-activity Relationship Studies In Et-18-och 3 -Indumentioning
confidence: 99%
“…This may allow treatment with a few doses. Alkyl-PCs are slowly metabolized by phospholipases to form products such as choline and long-chain alcohols that are physiological metabolites and can be recycled into phospholipids (9). Although alkyl-PCs as pure substances are effective and may accumulate in the affected organs, they cause some side effects.…”
Section: Discussionmentioning
confidence: 99%